Is Facebook eroding the public agenda? Evidence from survey and web-tracking data - Cardenal, AS; Galais, C; Majo-Vazquez, S (Oxford University Press, 2018)
Preserving a common public agenda positively affects social integration, minimizing social cleavages and polarization. Although social media are known for fragmenting the media environment, research has not devoted much attention to their effect on the public agenda. This article addresses whether consuming news through Facebook shapes individual agendas that diverge from the set of most important problems (MIPs) as perceived by the general public. Our research design combines survey and Web-tracking data to analyze how Facebook-referred news consumption influences individual consumers’ agendas. We find that when Facebook is a relevant news referral, people are less likely to mention the top MIPs for a representative sample of the Spanish population. We discuss the implications of our findings for the public agenda.